What works in distance learning : guidelines - O'Neil, Harold F., 1943- (Emerald Publishing Limited : Information Age Pub., 2005)
This book documents progress to date in what works in distance learning (DL). An overriding goal of this effort was to create a robust and clear set of design guidelines to support the next generation of DL training. The book is targeted mainly toward the research and program management communities. A companion book contains a set of lessons organized by guideline area. The lessons depict specific guideline areas in terms of how a particular guideline would look instantiated in a lesson.